PHOTOPHORESIS OF FLAVONOIDS IN COMPREHENSIVE TREATMENT OF PATIENTS WITH GENERALIZED PERIODONTITIS - I.Z. Chubiy; M.M. Rozhko (Ukrainian Medical Stomatological Academy, 2015)
The aim of the study was the new approach to methods of treatment of patients with generalized periodontitis by adding laser radiation and quercetin to the complex therapy. Scientists suggest that the use of physical therapy is necessary with almost all forms and stages of development of generalized periodontitis (GP) to diagnose illness symptomatic treatment, adjuvant therapy, prevention of disease in persons living under ecologically unfavorable conditions. Important features of physiotherapeutic treatment are stimulation of non-specific tissue reactivity and protective properties of the organism. After their usage activity of the elements of connective tissue and phagocytic activity of leukocytes are increased, tissue regeneration processes are accelerated, the application of laser therapy with quercetin promote recovery of antioxidant system, normalization of cell membrane potential and improving oxygen uptake by tissues become evident. We examined 90 patients with generalized periodontitis living in polluted areas of the Carpathians. All patients were administered the complex therapy commonly recommended for treating patients with generalized periodontitis: 1A group (22 people), 1B group (23 people) of patients with generalized periodontitis on I and II stage of development, respectively. Patients of the 1st group were applied periodontal applications of quercetin as a gel under an individual silicone tooth-gingival sealed end. Patients of 2A group (23 people), 2B group (22 people) with generalized periodontitis on I and II stage of development, respectively, were applied quercetin gel onto the mucous membrane of the gums where it was activated by laser irradiation. For the purpose of comparative characteristics of two groups there were performed the index evaluation of periodontal tissues, biochemical blood tests, X-rays, ultrasound examination of the tissue of jaw bone. The results have showed that the use of laser irradiation combined with quercetin in the complex treatment of patients with generalized periodontitis stimulates metabolic processes in periodontal tissues, reduces cyanosis, edema of periodontal tissues. The results have shown that the use of laser therapy in the complex treatment of patients with GP of the I-II stage of development provides reliable improvement of clinical efficiency of the treatment. Complex treatment of patients with generalized periodontitis using gel quercetin, which was activated by laser irradiation, shows significantly higher treatment efficiency over basic therapy and other methods of applying laser irradiation by clinical indicators.